2007
DOI: 10.1538/expanim.56.119
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetic Properties of Methamphetamine in Rats with Previous Repeated Exposure to Methamphetamine: The Differences between Long-Evans and Wistar Rats

Abstract: Repeated treatment with methamphetamine (METH) causes long-term behavioral changes, so-called behavioral sensitization (BS), in humans as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Although this was not a main research question from this study, this effect was observed here, specifically and exclusively in LER females. Strain differences in response to amphetamine have been observed previously 21 , 22 , 24 , 25 . This strain and sex specific effect in response to amphetamine may be the result of the interplay between the stress system and monoaminergic function, which has been posited to explain differences in response to amphetamine between two other strains of rats, Fisher 344 and Lewis 69 , 70 .…”
Section: Discussionsupporting
confidence: 60%
“…Although this was not a main research question from this study, this effect was observed here, specifically and exclusively in LER females. Strain differences in response to amphetamine have been observed previously 21 , 22 , 24 , 25 . This strain and sex specific effect in response to amphetamine may be the result of the interplay between the stress system and monoaminergic function, which has been posited to explain differences in response to amphetamine between two other strains of rats, Fisher 344 and Lewis 69 , 70 .…”
Section: Discussionsupporting
confidence: 60%
“…This was exclusively observed in LER females. Strain differences in response to amphetamine have been observed previously 19, 20, 22, 23 . This strain and sex specific effect in response to amphetamine may be the result of the interplay between the stress system and monoaminergic function, which has been posited to explain differences in response to amphetamine between two other strains of rats, Fisher 344 and Lewis 64, 65 .…”
Section: Discussionsupporting
confidence: 60%
“…Meth is rapidly absorbed from the peritoneum and then eliminated from the blood with a profile closely resembling a single-exponential process (23,76). Our data do not contain independent information about the volume of distribution.…”
Section: Model Constructionmentioning
confidence: 62%